STUDY OF THE PROPERTIES OF PROTIC IONIC LIQUIDS TO BE APPLIED IN THE ENHANCED OIL RECOVERY - G. F. D. Ferreira; C. B. M. Lima; S. Mateddi; L. C. L. Santos; A. K. C. L. Lobato (The Journal of Engineering and Exact Sciences)
The oil industry faces challenges with reservoir oil retention after years of exploration.  Therefore, recovery methods have been developed to produce residual oil, such as chemical methods (CEOR). Recently, ionic liquids have been gaining in visibility and it is expected that at CEOR, the Ionic Liquid (IL) will decrease the Interfacial Tension (IFT) between oil and water and increase the viscosity of the injected fluid. The aim of this paper is to study the ionic liquid [2HEA] [Hx] in order to evaluate the influence of its concentration and the salinity on the interfacial tension between oil and a solution of ionic liquid, through the statistical designing of experiments. It was verified that the IL [2HEA] [Hx] was able to decrease the interfacial tension between oil and the water solution and that both the ionic and salt concentrations were significant for the reduction of interfacial tension.